TINJAUAN YURIDIS TERHADAP PRAKTIK PERDAGANGAN OBAT SUBSTANDAR OLEH BIDAN - Hasudungan Sinaga (IBLAM Law Review)
This study is entitled juridical review of substandard drug trade practices by midwives: A Case Study of Decision number 1406/Pid.Sus / 2020 / Pn.Mdn. with the formulation of the problem of how criminal acts against substandard drug trafficking practices by midwives in the perspective of Criminal Law and how the consideration of judges. Using normative juridical methods. In conclusion, in Medan District Court decision No. 1406/Pid.Sus / 2020 / PN Mdn, the judge used the legal basis of Article 62 paragraph (1) of the Indonesian law No. 8 of 1999 regarding consumer protection and impose a fine of Rp5, 000, 000.00. According to the authors, the sanction given by the judge is considered too light when compared with the level of objection of the defendant who has been troubling and endangering others. More precisely, Article 196 of Law No. 36 of 2009 was considered more suitable for trying this case, given the defendant's profession as a midwife, so the appropriate sanctions should have been based on the health law, since the act of trafficking in substandard drugs committed by midwives is a criminal offense in the field of Health.